Effect of responsibility accounting on financial and social performances of branch expansion of microfinance institutions in the CamCCUL network, Cameroon - Kenah, Geah Henry; Bello; Mohe, Eugène (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: Microfinance Institution (MFI) branch expansion plays a critical role in enabling these institutions to achieve double bottom line objectives. However, this expansion strategy has introduced some management challenges pointing to responsibility accounting (RA). This study seeks to investigate the effect of RA on the financial and social performance of MFIs in the CamCCUL network, Cameroon.Methodology: The study adopted the quantitative research method using questionnaires to collect data from a sample of 86 MFIs selected through convenience and simple random techniques. Robust OLS regression was employed to analyse data.Results and conclusion: Results indicate that for financial performance, assigning responsibilities and delegating authority (ARDA), allocating costs and revenues for controllability (ACRC) and establishing performance measurement targets (EPMT) were statistically insignificant while performance evaluation (PE) and performance incentive systems (PIS) were statistically significant. On social performance, ACRC, EPMT and PIS were statistically insignificant, whereas ARDA and PE were statistically significant. The study concludes that MFIs should pay rigorous attention to RA principles and integrate them into their strategic plans to ensure that accountability and transparency drive overall institutional performance. The study recommends that, MFIs should conduct periodic performance appraisals and use results for cost allocation, decision-making and promotion; incentive systems should be tied to measurable performance results to motivate staff towards congruency.Implication of findings: The study has implications for policymakers to regulate and enforce RA implementation for business sustainability across all sectors and enable MFIs to enhance accountability and expansion complexity management as well as narrow the existing literature gap on RA in Cameroon.
Keywords: Responsibility accounting; Decentralisation; Accountability system; Microfinance sector performance; Microfinance branch expansion; CamCCUL network